PERGESERAN FUNGSI PERDAMAIAN (ISHLAH) DALAM RUMAH TANGGA PADA PROSES PERCERAIAN DI SEBERANG KOTA JAMBI - Muhammad Irsyad; rahmi hidayati; robi'atul adawiyah (Fakultas Hukum, Universitas Samudra, 2025)
This study examines the shift in the function of peace (ishlah) in households during the divorce process in the Seberang Kota Jambi area. The high divorce rate in Indonesia, including in Jambi, indicates that peace efforts that should be the last bastion of household integrity are not running optimally. In the context of the Jambi Malay community which is thick with Islamic customs and sharia values ​​(Adat Bersendi Syarak, Syarak Bersendikan Kitabullah), ishlah has a crucial role as a conflict resolution mechanism based on deliberation and family. However, the reality in the field shows a change in the practice of ishlah along with the increasing legal formality in the divorce process. The results of the study show that the function of ishlah has shifted from its ideality as a substantive effort to a mere formality in the divorce process in Seberang Kota Jambi. Peace efforts at the family or customary level tend to be less effective due to the lack of commitment from the disputing parties. Mediation in the Religious Court, although mandatory, is often perceived as only an administrative procedure that is less successful in restoring harmony. The main factors driving this shift include: increasing individualism in society, the dominance of positive legal channels of the Religious Court which are considered more certain, and the weakening of the role and authority of the Jambi Malay Customary Institution (LAM) or community leaders in intervening in domestic conflicts. This shift has an impact on the high divorce rate and thus has the potential to cause more severe psychosocial impacts for the parties involved.